Determinants of competitiveness in the IT sector in the Kraków cluster as a part of creative industries - Mamica, Łukasz (Journal of Public Governance, 2015)
The value of key firms’ assets in a global competitive economy has a crucial role in their development. In creative industries, these assets mainly have a non-physical character. The paper presents the results of research in 223 firms in the IT sector in Kraków. The research was questionnaire-based and aimed to assess the importance of factors which determine the decision to create a firm in this city. Another aspect of the research is connected with the estimation of the value of factors which, in the opinion of their managers, contribute to their firms’ competitiveness. Kraków is a city where the IT sector is well developed (with research centres of such multinational companies like IBM, Google, Motorola, ABB), and the research studies the nature of interactions among the firms in the sector. The role of institutional environment in the firms’ development as an important factor in their growth is also researched, as are evaluations of the profits made by the firms as a result of cooperation with universities, R & D units, other IT firms, and personal relations. Special attention is paid to institutional aspects of direct government stimulation of innovativeness and knowledge transfer.